The discursive field around the voluntary interruption of pregnancy. The construction of law and resistance in Argentina - Batres, Lisi (2025)
The approval of the Voluntary Termination of Pregnancy Law in Argentina was a milestone in the fight for women’s rights, but the debate was not settled and continued to leave traces in the media agenda. The objective of the research is to identify and characterize, in an exploratory manner, the discursive field that is articulated in the journalistic discourse from the implementation of said law. At a methodological level, key analysis categories were incorporated to identify the nodal points of the discourse: agenda, public opinion and media coverage. Among the results, the continuity and strengthening of the arguments by those who seek to strengthen women’s rights and the intention of those who defend the right to life to blur the polarization for/against the law, in force throughout the parliamentary debate, stand out.